(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Hepatitis infection has remained a reoccurring public health challenge. The seroprevalence of Hepatitis B and Hepatitis C virus infection among inmates in Lafia correctional service, Nasarawa State, Nigeria was assessed. Blood samples of 120 inmates were screened using the HBV surface antigen (HBsAg) rapid test Dip-strip and HCVAb plus rapid test strip. Socio-demographic and risk factors were analyzed using Fishers exact test binary logistics regression (p ≤ 0.05). Inmates were 29.16 % HBV and 8.3% HCV seropositive. Male inmates were 30% HBV and 8.18% HCV and females were 20% HBV and 10% HCV seropositive. Inmates ≥ 40 years and married inmates are more likely to be infected with HBV and HCV infections. Illicit drug use and incarceration above 5 years were risk factors significant for HBV and HCV prevalence. The high seroprevalence and risk factors of HBV and HCV infections among inmates needs prompt sensitization, screening and vaccination programmes.